Efektivitas Tanda Tangan Elektonik Pada Akta Yang Dibuat Oleh Notaris - Albaaits, Aushof; Turisno, Bambang Eko (Program Studi Magister Kenotariatan, Fakultas Hukum, Universitas Diponegoro, 2023)
AbstractThe electornic system is used to explain the existence of an information system which the application of information technology based on telecommunicaton network and electronic media. A digital signature is a.n. electronically generated signature that functions the same as a regular signature on paper documents. Sudikno Mertokusumo gives the definition of a certificate as evidence that is signed, which contains events that form the basis of a thing or an engagement, which was made from the beginning intentionally for proof. As a public office holder, a notary has the authority to inaugurate various certificate as long as it is not under the authority of other officials. The theory of this research is the triadism law theory which was initiaded by Gustav Radburch, which contains the principle of justice, and the principle of legal certainty. The theory of legal protection was initiated by Roscue Pound which says “the law is a social engineering tool and the writing method used is normative juridical. The results of this study are that digital signature have benefits are authenticity (guaranteed exstence), integrity (cannot be modified), non-repudiation (cannot be denied its existence), and confidentiality.Keyword: digital signature; certificate; notaryAbstrakSistem elektronik berfungsi untuk menerangkan posisi sistem informasi sebagai implementasi dari teknologi informasi menggunakan media elektronik dan jaringan telekomunikasi. Tanda tangan elektronik dilakukan secara elektronik yang memiliki fungsi yang sama dengan tanda tangan biasa. Sudikno Mertokusumo menjelaskan bahwa akta merupakan alat bukti yang disertai dengan tanda tangan, sebagai bukti bahwa telah terjadi perikatan. Dalam menjalankan profesinya, Notaris berhak untuk mengesahkan segala akta kecuali akta yang menjadi wewenang lembaga lain. Studi ini menggunakan Teori Triadism Law dari Gustav Radburch, yang di dalamnya memuat asas kemanfaatan hukum, keadilan, dan kepastian hukum. Selain itu juga teori dari Roscue Pound mengenai perlindungan hukum yang menerangkan bahwa hukum adalah media rekayasa sosial, dimana metode penelitiannya yaitu yuridis normatif. Hasil studi ini menyimpulkan bahwa tanda tangan elektronik berguna sebagai authenticity (terjaminnya keberadaannya), integrity (tidak dapat dimodifikasi), non-repudiation (tidak dapat disangkal keberadaannya), dan confidentiality (bersifat rahasia).Kata kunci: tanda tangan elektronik; akta; notaris